2010
DOI: 10.1111/j.1365-2621.2010.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid turbidimetric method for determining catechins in beverages

Abstract: We have developed a simple and rapid turbidimetric method to determine catechins based on the fact that many polyphenols produce hydrogen peroxide in an alkaline environment and that hydrogen peroxide oxidises cerium to generate cerium oxide precipitates. Four catechins (epicatechin, epigallocatechin, epicatechin gallate, epigallocatechin gallate) aggregated with these precipitates to form massive precipitates with increased turbidity. The catechins solution (0.18 mL) was mixed with 0.02 mL of 1% CeCl 3 soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The ferrous tartrate method is more selective than the Folin-Ciocalteau method, and is unaffected by the coexistence of reducing agents, such as ascorbic acid [14]. It is being used by researchers for the determination of tannins in tea [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ferrous tartrate method is more selective than the Folin-Ciocalteau method, and is unaffected by the coexistence of reducing agents, such as ascorbic acid [14]. It is being used by researchers for the determination of tannins in tea [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…reduction of expenditures on samples and reagents. Several studies have been reported in the literature using automated flow systems for analysis of tannins in tea samples using both the turbidimetric [10,19] and ferrous tartrate [14][15][16][17][18] methods. But it would be interesting to have an automatic system capable of allowing the analyst to choose, depending on the reagents available in the laboratory, determine tannins using the same manifold and selecting one of these methods via software.…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on the detection of large aggregates generated from the reaction of cerium and H 2 O 2 , which is generated by EGCg in alkaline environments, by electron microscopy. 14,15) Amounts of catechins adsorbed on the cell surfaces of Gram-positive bacteria, including Staphylococcus aureus and Bacillus subtilis, which are highly susceptible to catechins, are larger than those on Gram-negative bacteria, such as Escherichia coli, relatively resistant to catechins. 15) Among catechins examined to date, EGCg has the most potent antibacterial activity against E. coli.…”
mentioning
confidence: 99%
“…We obtained a high speed of analysis, thanks to the optimizations in the addition times and volumes of the fluids, in a microsystem that allowed a homogenization efficient and discrete measurements. Although the proposed system has been applied only to samples of green tea, the ferrous tartrate method can be also applied, in the same DIB-μFBA, for other types of tea, such as black tea, oolong tea, and white tea, where the tannin may vary between 10 and 100 mg L −1 [26][27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…The ferrous tartrate method is more selective than the Folin-Ciocalteau method [25] and is unaffected by the coexistence of reducing agents, such as ascorbic acid [26]. It is being used by researchers for the spectrophotometric determination of tannins in tea [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%